Analytical validation and the influence of nanoencapsulation in a forced degradation study of dihydromyricetin - Dalcin, Ana Júlia Figueiró; Roggia, Isabel; Ourique, Aline Ferreira; Raffin, Renata Platcheck; Santos, Roberto Christ Vianna; Gomes, Patrícia (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
A simple and rapid high-performance liquid chromatographic method was developed and validated for the determination of dihydromyricetin (DMY) in nanocapsule suspensions. The suspensions containing DMY showed mean particle diameter of 161 nm, polydispersity index less than 0.100, positive zeta potential between 11 and 14 mV, pH about 5.0, drug content of 100% and encapsulation efficiency of 80%. The method is carried out an RP-18 column with a mobile phase composed of acetonitrile-water (80:20 v/v) and a photodiode array detector at 290 nm. The method validation yields adequate results on linearity, specificity, precision, accuracy, and robustness. The samples (free and nanoencapsulated DMY) were subjected to following degradative conditions: acidic, alkaline, oxidative, thermal, and photolytic. Free DMY was most sensitive to alkaline degradation followed by oxidation, photolysis, thermal degradation and acidic hydrolysis. DMY nanocapsules suspensions were able to resist the thermal and photolytic degradation and reduced the extent of oxidative, alkaline and acidic hydrolysis. In conclusion, this method is suitable for measuring the DMY content of polymeric nanocapsules, it avoids the use of a buffer solution in the mobile phase, and it has a short retention time. Furthermore, this study showed for the first time that DMY can be protected from degradation by nanoencapsulation in polymeric nanocapsules. These results suggest that the use of DMY nanocapsule formulations have a great potential, and its use appears to be a promising strategy.